Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Sinar Suri Toyota - Margareth Sylvia Sabarofek (JFRES Journal of Fiscal and Regional Economy Studies, 2020)
PT. Sinar Suri Toyota is located in Manokwari Regency, West Papua Province. The research objective was to see whether compensation and work motivation had an effect on employee performance. This type of research is associative research using a quantitative approach method. The population is all employees in the workshop who work at PT. Sinar Suri Toyota Manokwari with a total of 32 people. However, at the time of data collection, there was a pandemic Covid-19 so that data retrieval via google was from. The data analysis technique used is multiple linear regression. To see the effect of the independent variable compensation and work motivation on the dependent variable employee performance through hypothesis testing. There are two ways used to measure the independent and dependent variables based on the t test and the F test. From the research results based on the parti al test (t test) for the variable compensation and work motivation on employee performance. For a significant value smaller than the error error (0.000> 0.05) and a significant value smaller than the error error (0.032> 0.05, so that H0 is rejected and Ha is accepted, meaning that partially the compensation and work motivation variables have a significant effect on the variable Employee performance While simultaneous testing (F test) of compensation and motivation variables on employee performance variables with a significant value smaller than the error error (0.000> 0.05) so that H0 is rejected and Ha is accepted, meaning that simultaneously, compensation and motivation greatly affect employee performance.